Hubungan Teori Hukum Dengan Praktik Penegakan Hukum Di Indonesia - Moh Holil (ASASI: Journal of Islamic Family Law, 2022)
Indonesia is a state of law, all state apparatus must act in accordance with the law and all people who live within the scope of Indonesia must obey the law. However, the applicable law in Indonesia has not yet shown its effectiveness, so that the purpose of the law has not been properly achieved. The term that is very familiar is "the law is blunt up and sharp down", such is the law in Indonesia. The law is very binding and cruel to the common people, while it is as if the law does not apply to those in power. The law for rulers and people with money can be traded, as evidenced by the rampant bribery that occurred in the State of Indonesia. So in the eyes of society, the law will fall when there is money. One of the problems of law enforcement among the people of Indonesia is that the public is generally against the law, the law is very far from the word justice and the apparatus is arbitrary towards the common people.